STRATEGI PENGEMBANGAN USAHATANI KANGKUNG ORGANIK DI KABUPATEN BOGOR (Jurnal Agribisnis Indonesia, 2018)
Organic farming was an agricultural farming techniques that rely on natural in without using of synthetic chemicals and organic agricultural farming was have provided health agricultural products, especially food that was safed for the health and consumers does not damage the environment. Based conventional farming systems such as the high energy input of chemical fertilizers and pesticides can damage and lower productivity of the soil. Soil degradation and environment damage destruction is the massive impact of the green revolution program in the 1980s. A combination of Internal factors (IFE) and external (EFE) matrix produces IE (Internal-External). SWOT (Strength, Weakness, Opportunities, Threats) of the organic farming water spinach in Bogor regency. Learning the best strategies in the analysis with Matrix QSP (Quantitative Strategic Planning). Based on the analysis of the activity of farming and the analysis of income from 500 m2 in 1 year only farmers have sold water spinach in market organic until 1,728 kg price of products 6.000 IDR and 2,472 kg had sold in traditional market at a price of 2.500 IDR. However, this shows that the farming of organic water spinach has financially profitable enough and will be more profitable when the entire water spinachcan hade been sold to the organic market. The results of the analysis of strategies using IE Matrix, SWOT Matrix and QPS Matrix acquired three most important strategies to be implemented: 1) "Strengthen and improve farm management institutions" (TAS value = 6.87); 2) Developing of human resources in the post-harvest handling (TAS value = 5.85); and 3) Extend the market network (TAS value = 5.63).